The Influence of Entrepreneurship Education on Innovation Capability among Chinese Undergraduate Students in Covid-19 Pandemic Era: A Framework of Analysis - Lei, Jianqiang; Hock, Oo Yu; Asif, Mahbub Karim (2020)
The recent global outbreak of COVID-19 epidemic crisis has posed a health and economic dual threat to countries and societies around the world, and before COVID-19 global spread, economic growth in almost all countries had slowed in the context of a tense trade war between the United States and China. In this spreading global pandemic, unemployment and stagnation of international trade have caused great economic pressures to many countries, especially China as a big exporter. This paper aimed at finding out the influence of entrepreneurship education on innovation capability among Chinese undergraduate students, the empirical research method is utilized in this study, 400 senior undergraduates from 3 universities in China are surveyed by questionnaires, all data collected will be analyzed by SPSS 20 and Amos 21. Many schools and universities around the world have adopted online education tools of the blended learning approach to mitigate this pandemic shock of the education industry. Nowadays, the competition among the big countries in the world is mainly focused on the technical barriers and innovation capability, according to the Triple Helix Model of Innovation that three main stakeholders in entrepreneurship ecosystem: government, university and industry is very important to the innovation. Finding indicated that the institutional environment and supporting infrastructure have a significant impact on student’s innovation capability in the three dimensions of entrepreneurship education. Therefore, the Chinese universities should combine the innovation-driven entrepreneurship education program, strengthen the supporting of institutional environment and infrastructure that enhance the student’s innovation practice ability with the human capital and social capital.